A composite lymphoma combining a Hodgkin lymphoma and a marginal zone lymphoma transformed into a diffuse large B‐cell lymphoma. Issue 12 (22nd October 2018) - Auditeau, Claire; Lambotte, Olivier; Feriel, Joffrey; Lazure, Thierry; Turhan, Ali; Aumont, Cédric
Key Clinical Message: Composite lymphoma is defined as the occurrence of two or more distinct lymphoma types in a single anatomic site. We report a case of Richter syndrome with both Hodgkin lymphoma and non‐Hodgkin lymphoma in the bone marrow. This diagnostic was suspected because of discrepancies between histological and cytological results. Abstract : Composite lymphoma is defined as the occurrence of two or more distinct lymphoma types in a single anatomic site. We report a case of Richter syndrome with both Hodgkin lymphoma and non‐Hodgkin lymphoma in the bone marrow. This diagnostic was suspected because of discrepancies between histological and cytological results.